2017
DOI: 10.1530/eje-17-0047
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular events in patients with mild autonomous cortisol secretion: analysis with artificial neural networks

Abstract: Cortisol after 1 mg-DST is independently associated with the CVE occurrence. The ANNs might help for assessing the CVE risk in AI patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
55
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 39 publications
(62 reference statements)
3
55
0
1
Order By: Relevance
“…Finally, a recent report on arterial stiffness in CS reported structural changes in the arterial wall occurring independently of blood pressure levels (28). Recent studies suggest that even patients lacking the full clinical picture of CS having an adrenal incidentaloma and a non-suppressed cortisol after DST suffer from increased cardiovascular events and mortality when compared to NFA (5,7,29,30). To our knowledge, this is the first study evaluating the relationship between pACS, LV function and structure and arterial stiffness and the first to describe a dose-response relationship between post-DST cortisol and LVMI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a recent report on arterial stiffness in CS reported structural changes in the arterial wall occurring independently of blood pressure levels (28). Recent studies suggest that even patients lacking the full clinical picture of CS having an adrenal incidentaloma and a non-suppressed cortisol after DST suffer from increased cardiovascular events and mortality when compared to NFA (5,7,29,30). To our knowledge, this is the first study evaluating the relationship between pACS, LV function and structure and arterial stiffness and the first to describe a dose-response relationship between post-DST cortisol and LVMI.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the ERGO trial (Endocrine Cardiomyopathy in Cushing Syndrome: Response to Cyclic GMP PDE5 inhibitOrs) was designed. Retrospective analysis unexpectedly revealed that also asymptomatic patients with adrenal adenomas and low-grade autonomous cortisol secretion suffer from a higher rate of CV events and mortality than patients with normal HPA axis suppression (5,6,7). Despite these epidemiological associations, only two small studies investigated morphological and functional changes to the CV system in patients with mild hypercortisolism (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Cut‐off points for exclusion of hypercortisolism were modified over time as evidenced by the clinical repercussion of excess cortisol, with decreasing levels in DST (138 nmol/L [5.0 μg/dL], 83 nmol/L [3.0 μg/dL] and currently being excluded at lower levels or equal to 50 nmol/L [1.8 μg/dL]) . Morelli et al using analysis with neural networks identified that the cut‐off of cortisol levels after 1 mg‐DST above or equal to 138 nmol/dL (1.8 μg/dL) was the most accurate for detecting patients with increased CVD risk. These authors identified that in AI patients with cortisol levels after 1 mg‐ DST above 41 nmol/L (1.5 μg/dL), the CVD prevalence progressively increases with increasing 1 mg‐DST.A large cross‐sectional study identified that progressively increased cortisol hypersecretion differently predict major metabolic and cardiovascular outcomes, regardless of other potential risk factors .…”
Section: Discussionmentioning
confidence: 99%
“…Cut-off points for exclusion of hypercortisolism were modified over time as evidenced by the clinical repercussion of excess cortisol, with decreasing levels in DST (138 nmol/L [5.0 μg/dL], 83 nmol/L [3.0 μg/dL] and currently being excluded at lower levels or equal to 50 nmol/L [1.8 μg/dL]) 1,42,43. Morelli et al44 using analysis with neural networks identified that the cut-off of cortisol levels after 1 mg-DST above or equal to 138 nmol/dL (1.8 μg/dL) was the most accurate for detecting patients with increased CVD risk. These authors iden-2% and specificity 88%) in predicting cardiovascular risk in patients with adrenal adenomas.…”
mentioning
confidence: 99%
“…8 Longitudinal retrospective studies demonstrated that, as a group, patients with MACE had an increased prevalence of cardiovascular risk factors (eg, hypertension, type 2 diabetes mellitus (DM2), obesity and dyslipidemia), which lead to an increased cardiovascular mortality. [8][9][10][11] In comparison with patients managed conservatively, patients with MACE treated with adrenalectomy demonstrated a reduction in cardiovascular risk factors. 8 However, the selection of patients who might benefit from adrenalectomy is difficult.…”
Section: Introductionmentioning
confidence: 99%